pyFIRI — A free and open source Python software package of the non-auroral Earth’s lower ionosphere - Oleg Zolotov (Elsevier, 2021)
pyFIRI is a free and open source Python3 implementation of FIRI-2018, a model of the Earth’s ionospheric D-region. This region is one of the hardest to observe and model in contrast to other ionospheric layers. The FIRI-2018 is an updated version of the FT-2001 model included into the International Reference Ionosphere model, which is a de-facto standard ionosphere model. Originally, the FIRI-2018 model was provided as a set of tabulated values stored and distributed in the form of a Microsoft Excel file. The interested parties had to automate data manipulation themselves. pyFIRI provides an easy “pythonish” way to deliver, install, update, and use the FIRI-2018 model which is valuable for ionosphere investigations including radio waves propagation problems.